2018
DOI: 10.3233/ch-170301
|View full text |Cite
|
Sign up to set email alerts
|

Viscometer validation studies for routine and experimental hemorheological measurements

Abstract: Thorough validation studies are required before starting experimental and routine viscosity measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Approximately 0.5 ml of venous blood sample was used, which was processed at a controlled temperature of 37°C, in the Brookfield AMETEK brand viscometer, model DV2T LV CP (cone-plate), and BV values were expressed in poises (P); the measurement was performed in accordance with the existing regulations 14,15 .…”
Section: Blood Viscosity Measurementmentioning
confidence: 99%
“…Approximately 0.5 ml of venous blood sample was used, which was processed at a controlled temperature of 37°C, in the Brookfield AMETEK brand viscometer, model DV2T LV CP (cone-plate), and BV values were expressed in poises (P); the measurement was performed in accordance with the existing regulations 14,15 .…”
Section: Blood Viscosity Measurementmentioning
confidence: 99%
“…If samples cannot be measured in this period, they are usually placed in the refrigerator and measured on the next business day. Still in the study by Kovacs et al, 25 the BV was significantly lower after 3 hours at 37°C in the Shear rates of 50 and 100 s‐1. The study by Horner et al 26 found similar results, as they identified a time of approximately 3 hours as the maximum time after the initial test so that accurate rheological tests could be performed on blood samples.…”
Section: Discussionmentioning
confidence: 78%
“…Kovacs et al 25 concluded that samples can be stored for up to 48 hours, at 4°C, without affecting the measured values, but storage at 37°C for several hours is not recommended. Therefore, when storing blood samples, one should refrigerate them when the storage time is long, above four hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary and rotational viscometers, as well as falling body viscometers, are the most frequently used for blood viscosity measurements. For example, the Brookfield rotational viscometer with the UL adapter for low dynamic viscosity in the range from 1 to 10 mPa•s [19] allows measuring fluid viscosity as a shear rate function [24,25,18,26,17,27]. The test fluid capacity for this adapter is approximately 16 ml [19] which is a significant disadvantage.…”
Section: Literature Reviewmentioning
confidence: 99%